PARTISIPASI MASYARAKAT DALAM PEMBANGUNAN FISIK DI DESA NEGARA NABUNG KECAMATAN SUKADANA KABUPATEN LAMPUNG TIMUR DALAM PEMBANGUNAN (Administratio, 2018)
ABSTRACT. This article aims to describe community participation in village development. The study was conducted with a descriptive qualitative approach. The results of the study show that in the development there is a sense of belonging between the people. Formed a sense of dependence and attachment (sense of belonging and sense of commitment) to the purpose of life. Created skills to adjust to changing circumstances. There is a real manifestation of village development and the existence of initiatives among community members.